Children of the fox - Sands, Kevin (Sands, Kevin. Thieves of shadow., 2021)
Five young criminals join forces to pull off the crime of the century involving a magical artifact belonging to the High Weaver, the world<U+0092>s most powerful sorcerer. They are all used to working alone, but they must learn to trust each other in order to get the job done.